ERRγ, a Novel Biomarker, Associates with Pathoglycemia of Endometrial Cancer to Predict Myometrial Invasion. (21st June 2022) - Tong, Yao; Huang, Meimei; Chen, Lili; Lei, Huifang; Lin, Hao; Mao, Xiaodan; Sun, Pengming
Abstract : We aim to investigate the correlation between the expression of estrogen-related receptor γ (ERR γ ) and endometrial cancer (EC) progression and to evaluate the potential of ERR γ as a new biomarker for EC diagnosis. We analyzed the ERR γ expression profile and the correlation with the corresponding clinical characteristics of EC samples from The Cancer Genome Atlas (TCGA), the Clinical Proteomic Tumor Analysis Consortium (CPTAC) databases, and the International Cancer Genome Consortium (ICGC) databases. Immunohistochemical (IHC) analysis was conducted on tissue samples, and enzyme linked immunosorbent assay (ELISA) was used in serum samples to detect the levels of ERR γ . The diagnostic performance of ERR γ proteins was assessed using the receiver operating characteristic (ROC). ERR γ showed notably higher expression in EC tissues than in normal endometrium tissues (P < 0.001 ), which was consistent with the result of TCGA. Overexpression of ERR γ was significantly associated with deep myometrial invasion of EC (P = 0.004 ), and fasting blood glucose (FBG) was higher in EC patients with deep myometrial invasion than in those with superficial myometrial invasion (P = 0.040 ). Further analysis using ELISA showed that the serum ERR γ level was positively correlated with FBG ( R  = 0.355, P < 0.001 ). ERR γ is overexpressed in EC and may be involved in regulating glucose metabolism and promoting myometrial invasion of EC. In addition, the area under the ROC curve (AUC) for ERR γ was 0.834, in distinguishing EC patients from healthy individuals, presented 84.0% and 80.0% sensitivity and specificity, respectively, and serum ERR γ has a good diagnostic performance in distinguishing EC patients from healthy people and may be a promising noninvasive biomarker in EC.